Health information seeking behavior of Filipinos, 45-years-old and above with cardiovascular diseases living in Quezon City - Landicho, Quiella A.; Santos, Mark Anthony A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
The rate of mortality caused by cardiovascular diseases continues to grow in the recent years not only in the Philippines but also worldwide. With this, a lot of people with cardiovascular diseases seek health information regarding their conditions. Hence, in an attempt to inhibit the increasing number of cases, and to lessen the mortality rate caused by cardiovascular diseases, it is vital to determine how people search for health information. The purpose of this study is to determine the health information seeking behavior of Filipinos, 45-years-old and above with cardiovascular diseases living in Quezon City.
A total of 35 respondents from different barangays in Quezon City were recruited in the study through chain referrals. The study employed the use of survey questionnaire to acquire the needed information. The questionnaire was adapted after the studies of Longo and his co-authors (2009), and of Zaide (2012) concerning health information seeking behavior. The survey questionnaire contained questions regarding the respondents' background information, the stages of their health information usage, their preferred health information sources, and the factors that influence their health information seeking behavior. Interviews were also conducted to obtain additional information. However, majority of the respondents chose not to participate in the interview due to their busy schedules.
The respondents were likely to seek health information from various sources to gain more insights about their cardiovascular diseases. Therefore, this made them active seekers of health information. All of the respondents also considered doctors as their primary source of health information. Next to doctors, they were likely to seek health information from their families, friends and from television programs. In contrast, the respondents were not likely to look for health information from libraries and reading centers. Factors such as trustworthiness of the source, comfort and security, and accessibility of the source influenced their health information seeking behavior.
Furthermore, the respondents were also deemed as passive receivers of health information as they inadvertently gained information from their friends and other people with the same condition as theirs. Recommendations on increasing the awareness of people on the available health information from several sources especially from the library were proposed.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Health behavior; Information behavior; Cardiovascular system -- Diseases